Peace Education Evaluation: Learning from Experience and Exploring Prospects - Hajir, Basma (In Factis Pax: Journal of Peace Education and Social Justice, 2019)
Review of Peace Education Evaluation: Learning from Experience and Exploring Prospects. Edited by Celina Del Felice, Aaron Karako and Andria Wisler, Information Age Publishing, Charlotte, North Carolina, 2015, 329 pp., (paperback), ISBN 1623969735, £79.50 (hardcover), ISBN 1623969743.